Academic Procrastination among University Undergraduates: Role of Self-Efficacy and Self-Motivation - Mohd Zaid, Najmi Najiha; Mat Isa, Nura'in; Afnizul, Afina Nazira (Selangor Humaniora Review, 2021)
Academic procrastination occurs with students, regardless of their level of education. Procrastination is the tendency to avoid the completion of mandatory tasks and duties handed to them. At the higher education level, academic procrastination happens when an undergraduate delay the completion of provided tasks within the supposed period. This paper studied the role of self-efficacy and self-motivation towards academic procrastination among university undergraduate students. This study was carried out using a quantitative survey questionnaire on undergraduate students studying in a local private institution of higher education. Eighty respondents were gathered according to their clusters labelled high CGPA and low CGPA. This study used tools such as Academic Procrastination Scale (APS), Academic Self-Efficacy Scale (ASES), and Academic Motivation Scale (AMS), English versions. Results show that high achievers are driven by intrinsic motivation. They are internally driven to do something they are interested in and not rely on external motivation such as rewards, compliments, and low CGPA undergraduates.